2020
DOI: 10.1063/1.5135093
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization of the nitrocellulose-based visco-hyperelastic binder in polymer bonded explosives

Abstract: A rheological constitutive model is required to characterize the behavior of a nitrocellulose-based material used as a binder in polymer bonded explosives. The behavior of the binder is extremely important as it heavily influences the mechanical response of the polymer composite; this is due to the binder having stiffness five orders of magnitude lower than the stiffness of the explosive crystals. Determination of the material model parameters is not straightforward; a constitutive law that will capture the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The material, which will be referred to as PBX-1 in this study, is a polymer-bonded explosive composing of 88% volume fraction of HMX crystals and 12% volume fraction of a polymeric binder, specifically a nitrocellulose-based visco-hyperelastic polymer [14]. The binder consists of Nitrocellulose (NC), plasticiser (a mixture of dinitroethylbenzene and trinitroethylbenzene) and stabiliser in the ratio of 1:8:0.02, respectively, with good adhesion properties [14]. The composite has a broad spectrum of HMX crystals sizes to achieve the high volume fraction (88%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The material, which will be referred to as PBX-1 in this study, is a polymer-bonded explosive composing of 88% volume fraction of HMX crystals and 12% volume fraction of a polymeric binder, specifically a nitrocellulose-based visco-hyperelastic polymer [14]. The binder consists of Nitrocellulose (NC), plasticiser (a mixture of dinitroethylbenzene and trinitroethylbenzene) and stabiliser in the ratio of 1:8:0.02, respectively, with good adhesion properties [14]. The composite has a broad spectrum of HMX crystals sizes to achieve the high volume fraction (88%).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that the PBX material properties depend on the binder system, volume fraction and crystal size distribution [1,[9][10][11][12][13]. The polymer binder system is often challenging to characterise owing to its highly nonlinear, time-dependent behaviour [10,14]. PBX materials with a higher binder content undergo more substantial strain to failure, while those with smaller crystal sizes for the same volume fraction are stronger [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of viscoelasticity and hyperelasticity is available in commercial finite element software. The development and application of visco-hyperelastic models is topic of a large number of current publications, e.g., [9][10][11][12]. In a preceding work of the author [13], an attempt was made to identify a visco-hyperelastic model using a minimal number of experiments.…”
Section: Combination Of Hyperelasticity and Viscoelasticitymentioning
confidence: 99%
“…Solving the system of (7), (10), and (11), the volume change can be expressed in terms of the bulk modulus and the measurable quantities stretch and nominal stress:…”
Section: Stress Transformation and Compressibilitymentioning
confidence: 99%
“…The behavior of the adhesive is extremely important because it will affect the mechanical response of the polymer composite. The stiffness of the adhesive is five orders of magnitude lower than the stiffness of the explosive crystal [24]. Parker et al [25] find that there is some safety benefit for having binders in HMX, especially when the binder is thermally stable.…”
Section: Introductionmentioning
confidence: 99%